Viés de sexo na abordagem das tendinopatias nos membros inferiores: uma análise abrangente por meio de revisão sistemática - Cavalcante, Mariana (2025)
Background: Women are historically underrepresented in clinical research, including studies on lower limb tendinopathies, compromising the development of effective and personalized treatments. Tendinopathies such as Achilles, patellar, hamstring, and gluteal tendinopathies are prevalent conditions that impact functionality and quality of life, especially in physically active populations. Objective: This systematic review aims to analyze randomized controlled trials (RCTs) on non-surgical treatments for lower limb tendinopathies to assess the extent to which sex- related differences are considered in clinical outcomes and treatment efficacy. Methods: A systematic search was conducted across multiple databases (CENTRAL, MEDLINE, EMBASE, and PEDro) for RCTs involving non-surgical treatments of Achilles, patellar, gluteal, and hamstring tendinopathies. Data extraction focused on participant characteristics, outcomes stratified by sex, and methodological quality (PEDro scale). A total of 198 studies were included, with only 4.5% conducting sex-specific analyses and 2.5% including only female participants. Results: Women represented 39.7% of the total participants. Studies with sex-stratified analyses reported differences in treatment responses. Women exhibited higher sensitivity to pain, lower tendon cross-sectional area, and reduced adaptive capacity to mechanical loading. Hormonal factors, particularly estrogen, negatively influenced tendon regeneration and elasticity. However, studies failed to detail the biological mechanisms underlying these differences. Conclusions: The persistent gender data gap limits the development of sex-specific clinical guidelines and effective treatments for tendinopathies. To address this disparity, future research should prioritize the inclusion of women, enforce sex-stratified analyses, and investigate hormonal and structural influences on treatment outcomes. Personalized therapeutic approaches are essential for equitable and effective care.